Revisão taxonômica e análise cladística do gênero Cyrtopholis Simon, 1892 (Araneae, Mygalomorphae, Theraphosidae) - Silva, Willian Fabiano da (2019)
Cyrtopholis is one of the five genera of Theraphosinae having a stridulatory apparatus located on the trochanters of the palp and/or on coxae of the legs. This is an important taxonomic character used for genus delimitation and their diagnosis. Cyrtopholis has a relatively large cast, with 24 species described for the Caribbean region and a dubious record for South America. The genus has never been taxonomically or phylogenetically reviewed and the original descriptions are old with generic information of Theraphosidae, hindering the knowledge of its real faunistic diversity and occurrence. The present thesis aimed to review the taxonomy and to test monophyly of Cyrtopholis and its relationship between morphologically similar taxa, such as Longilyra Gabriel 2014, Cubanana Ortiz, 2008, Phormictopus Pocock, 1901, Acanthoscurria Ausserer 1871 and Umbyquyra Gargiulo, Brescovit & Lucas, 2018, through cladistic analysis including at least the type species of these genera and representatives of the largest diversity of Theraphosinae as outgroup. The matriz was composed of 52 morphological characters (continuous and numeric) and 52 terminal taxa. Heuristic searches were implemented with and without implied weighing, by TNT computer program, generating one parsimonious trees. Longilyra resulted as an ingroup of Cyrtopholis in the resulted tree and the synonymy between these genera is proposed. Cyrtopholis has non-exclusive synapomorphies: presence of the stridulatory apparatus composed of claviform bristles in the trochanters of the palps and legs I, metatarsal flexion I in retrolateral branch of the tibial apophysis and presence of retrolateral tibial nodule of the palp and type I and III urticant setae on the dorsum of abdomen. Two new species are described from Cuba and four new species from the Dominican Republic. The female of Cyrtopholis agilis is described of which only the male was known of the Santo Domingo, four species of the eight described by Franganillo are redescribed, other four are considered species inquirenda or nomem nudum, due to lost holotypes. In addition, the five species types deposited at the British Museum of Natural History were diagnosed, tree of the Museum Comparative Zoology oh the Harvard, tree of the Museum Natural History of the Holguin, Cuba, two of the Senckenberg Museum, Frankfurt, Alemanha and one of the American Museum of Natural History, United States, totalling for the first time a review of all 24 species of the genus. And finally, a new genus of Cuba is proposed, according to the phylogeny presented.